PENGARUH DOMINASI PASAR DAN OTONOMI DAERAH PADA EFEKTIFITAS UU NOMOR 32 TAHUN 2009 (Kajian Perspektif Sosio Legal Studies) - M Muslih (Jurnal LEX SPECIALIS, 2010)
Abstract Indonesia community should be able to improve the life of him remember the grace of a great environment as the carrying capacity in the form of sea life, forests, grasslands and other abundant sources of mine. Our Constitution affirms that the natural wealth profusely used to memwujudkan welfare of the community, various policies have been taken to make it happen, but until this moment the poor swabs are not reduced and she became more irony. Policy of regional autonomy that comes with a variety kewenanagan basically aims for each area with its independence is able and willing to improve competitiveness in order to memujudkan welfare of the people through meraeka potential resources have, however unconsciously and tradition we have been accustomed to relying on the practices of capitalism and free markets.On the other hand the condition of the majority of our society in the region solely as an object in the "flow motion" so that the local economy if policy makers are not clever and smart in selecting and sorting policy, the policy of regional autonomy will only be enjoyed by a handful of elites and not change the fate of the people significantly. The birth of "tradition" competition authority periodically that require high cost, makes the position of natural resources (environment) as a strategic capital for the "life" nation and state, became seizure to satisfy the ambitions of an elite group of "five-yearly ritual." (Not a priority for the sake of people who should be empowered). The description in this paper gave birth to pessimism, will keingnan to live more feasible, both economically and health. People in a position sandwiched "is like falling down stairs" as beaten by the capitalists through the foot-hand in Indonesia and its own leaders (local leaders), and therefore government policy through the Environment Protection and Management to be difficult to implement in an optimal fashion.